Association of cardiac and non-cardiac chronic disease comorbidity on glycaemic control in a multi-ethnic population with type 1 and type 2 diabetes. Issue 1033 (26th August 2011) - Mehta, R L; Davies, M J; Ali, S; Taub, N A; Stone, M A; Baker, R; McNally, P G; Lawrence, I G; Khunti, K
Abstract : Aims: To determine the prevalence of chronic disease comorbidity in south Asians (SAs) and white Europeans (WEs) with diabetes and to quantify the relationship of cardiac disease comorbidity (CDCM) and non-cardiac disease comorbidity (NCCM) to glycaemic control in SAs and WEs with type 1 and type 2 diabetes mellitus. Methods: A cross-sectional study using a database of patients of SA (25.5%) and WE (74.5%) origin attending a specialist diabetes clinic in the UK between 2003 and 2005 (n=5664). Results: The prevalence of SAs and WEs with type 1 diabetes was 12% and 88%, respectively; for those with type 2 diabetes the prevalence was 30% and 70%, respectively. Overall, the prevalence of comorbidity in people with type 1 diabetes was 25.5% and with type 2 diabetes was 47%. NCCM was more prevalent in WEs than SAs (17.6% vs 12.8%, p<0.001). In type 2 diabetes, the prevalence of suboptimal glycaemic control was significantly greater in SAs compared to WEs with NCCM and CDCM (79% vs 62%, p<0.001; 78% vs 65%, p<0.001, respectively). SAs with type 2 diabetes and comorbidity had excess odds of suboptimal glycaemic control compared to WEs: OR 2.27 (95% CI 1.50 to 3.43) for those with NCCM and OR 1.91 (95% CI 1.49 to 2.44) for those with CDCM. Conclusions: The prevalence of CDCM is higher in SAs compared to WEs with type 2 diabetes, whereas the prevalence of NCCM is higher in WEs compared to SAs. Taking into account comorbidities, SAs (compared to WEs) with type 2 diabetes had an excess risk of having HbA1c ≥7% ranging from 1.86- to 2.27-fold. Further research is needed to identify the reasons for unfavourable metabolic conditions in SAs and also develop and evaluate interventions.